The Prevalence and Risk Factors for Gestational Diabetes Mellitus in the Expecting Outpatients of Mashhad University of Medical Sciences, Iran (2017-2018) - Kazem Saeedi; Ali Taghipour; Ehsan Mousa-Farkhani; Nasrin Milani (Reviews in Clinical Medicine, 2020)
Introduction: Diabetes is the most common metabolic disorder during pregnancy. Given the importance of the screening and treatment of gestational diabetes for the prevention of maternal and fetal complications, the present study aimed to evaluate the prevalence of gestational diabetes mellitus in the pregnant women covered by Mashhad University of Medical Sciences, Iran.Methods: This study was conducted on the women with pregnancy intention or confirmed pregnancy, referring to the health centers affiliated to Mashhad University of Medical Sciences during March 2017-September 2018. The patients with gestational diabetes mellitus were identified based on the latest WHO criteria in 2013. Data were collected on the conducted experiments and recorded in the integrated health information system (SINA). Data analysis was performed in SPSS version 25 using Chi-square and logistic regression.Results: During the study period, 2,710 women (4.3%) were diagnosed gestational diabetes mellitus. The mean age of the patients was 28.5656.379 years. In terms of the influential factors, significant correlations were observed between gestational diabetes mellitus and family history of diabetes (OR=4.278; P<0.0001), history of gestational diabetes mellitus (OR=3.880; P<0.0001), body mass index (OR=2.302; P<0.0001), history of macrosomia (OR=1.656; P<0.003), history of recurrent miscarriage (OR=1.759; P<0.007), and preeclampsia (OR=1.914; P<0.045). Conclusion: According to the results, the prevalence of diabetes in Mashhad city (4.3%) seems to be slightly lower than other areas. Special attention must be paid to the pregnant women with the influential factors of gestational diabetes mellitus through selective screening based on the risk factors of the disease.